2018
DOI: 10.5664/jcsm.6952
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis Intervention Effects on Sleep Outcomes: A Systematic Review

Abstract: Hypnosis for sleep problems is a promising treatment that merits further investigation. Available evidence suggests low incidence of adverse events. The current evidence is limited because of few studies assessing populations with sleep complaints, small samples, and low methodological quality of the included studies. Our review points out some beneficial hypnosis effects on sleep but more high-quality studies on this topic are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
(88 reference statements)
0
19
0
6
Order By: Relevance
“…A recent meta-analysis showed that hypnosis is a highly effective intervention for anxiety and is more effective when combined with other psychological interventions and various clinical applications [28]. Hypnosis is known to reduce acute and chronic pain [32][33][34][35][36] and improve sleep quality [37,38]. A variety of relaxation techniques have been investigated to improve the quality of sleep in ICU patients (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis showed that hypnosis is a highly effective intervention for anxiety and is more effective when combined with other psychological interventions and various clinical applications [28]. Hypnosis is known to reduce acute and chronic pain [32][33][34][35][36] and improve sleep quality [37,38]. A variety of relaxation techniques have been investigated to improve the quality of sleep in ICU patients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…aromatherapy, earplugs and masks, noise bundle) but results are not convincing in all studies [39,40]. One review of the literature showed that hypnosis seems to be a promising technique for management of sleep problems; however, more randomised studies are required to support these results [34]. Hypnosis is an efficient treatment in health care, and one that can save time and costs to healthcare providers in some instances [35,41].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing evidence base supports the efficacy and safety of clinical hypnosis in acute, chronic, and procedural pain, depression, anxiety, irritable bowel syndrome, and sleep problems. [46][47][48][49][50][51] Clinical hypnosis may also enhance the efficacy of other therapeutic approaches. 45,52,53 As part of an integrative intervention for chronic pain, the value of hypnosis is well documented in adults, and the research evidence for efficacy of pediatric pain management is increasing.…”
Section: Twisted In Painmentioning
confidence: 99%
“…Hipnoz klinisyenler ve hastalar için çekicidir çünkü kısa bir zamanda uzun süreli semptom iyileşmesi sağlayabilir. Ayrıca, bu yaklaşım hasta özelliklerine ve şikayetlerine göre uyarlanabilir (27). Son yıllarda; uyku bozukluklarının tedavisi için hipnoz kullanımına ilişkin çalışmaların sayısı gittikçe artmaktadır.…”
unclassified
“…Chamine ve ark. (27) 2018 yılında yaptıkları derlemede; dahil edilen çalışmaların %58,3'ünde uyku bozukluklarda hipnozun yararı olduğu gösterilmiştir. Hipnoz, uyku bozuklukları olan hastalar için potansiyel terapötik fayda sağlar.…”
unclassified